2011
DOI: 10.1002/ajmg.b.31170
|View full text |Cite
|
Sign up to set email alerts
|

ADHD in Dutch adults: Heritability and linkage study

Abstract: Attention deficit/hyperactivity disorder (ADHD) is a neurodevelopmental phenotype that persists into adulthood. This study investigated the heritability of inattentive and hyperactive symptoms and of total ADHD symptomatology load (ADHD index) in adults and performed linkage scans for these dimensions. Data on sibling pairs and their family members from the Netherlands Twin Register with genotype and phenotype data for inattention, hyperactivity and ADHD index (∼750 sib-pairs) were analyzed. Phenotypes were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 66 publications
2
21
0
1
Order By: Relevance
“…Low behavioral motivation, low social motivation, and inattention have been shown to be moderately heritable in both adults and children (Goldsmith, Buss, & Lemery, 1997; Saviouk et al, 2011; Sherman et al, 1997; Silberg et al, 2005; Takahashi et al, 2007), indicating possible parent-to-child transmission of these characteristics in biologically-related parents and children. Such parent characteristics (i.e., low behavioral motivation) may therefore influence child characteristics (i.e., low social motivation) through shared genetic influences.…”
Section: The Confound Of Genotype-environment Correlationmentioning
confidence: 99%
“…Low behavioral motivation, low social motivation, and inattention have been shown to be moderately heritable in both adults and children (Goldsmith, Buss, & Lemery, 1997; Saviouk et al, 2011; Sherman et al, 1997; Silberg et al, 2005; Takahashi et al, 2007), indicating possible parent-to-child transmission of these characteristics in biologically-related parents and children. Such parent characteristics (i.e., low behavioral motivation) may therefore influence child characteristics (i.e., low social motivation) through shared genetic influences.…”
Section: The Confound Of Genotype-environment Correlationmentioning
confidence: 99%
“…Though the exact causes of clinical ADHD are not known, medical studies find consistent evidence that the disorder has a neurobiological origin (Mathis et al 2014) and is genetically determined (Thapar et al 1999;Mathis et al 2014) with genetics contributing to about 60-75 % of cases (Cortese 2012;Faraone et al 2005). Despite the fact that ADHD appears quite stable and the majority of adolescents continue to experience its symptoms in (young) adulthood (Biederman et al 2007;Kan et al 2013;Saviouk et al 2011), most of what we know about its consequences for individual behavior is derived from research with children. Far less attention is paid to adult decision making and behavior (Young 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Familial clustering of adult ADHD was reported by Antshel et al [2009] who found in a sample of high IQ adults that ADHD was more prevalent in first degree relatives of adults with ADHD relative to controls (28% in family members of adults with ADHD versus 5% in family members of IQ matched controls). Only two twin family studies till date looked at the genetic influences on adult ADHD [Boomsma et al, 2010; Saviouk et al, 2011]. Both studies used the screening version of the Conners’ Adult Rating Scales [CAARS-S:SV; Conners et al, 1999] to assess inattentive and hyperactive symptoms and likely ADHD diagnosis(ADHD-Index) in a large sample of Dutch twins and their family members.…”
Section: Introductionmentioning
confidence: 99%